Constructive communications talking your way to success - Johnson, Dorothy R.; Caldwell, Sara Coover; Shreve, Daniel L.; Gardner, Edward T.; Sole, Diana; Damron, Jim (The communication series, 2004)
This program guides viewers through an E.A.S.Y. communication process. Students learn constructive communications by identifying the Effect they hope to achieve; understanding the knowledge and attitude of their Audience; explaining the Subject with specific and organized information; and seeing the positive effects of knowing and understanding Yourself.